AN EXAMINATION OF THE ROLE PLAYED BY NON-BRAHMANAS IN THE TEMPLE CENTERED BRAHMANIC SOCIAL ORDER DURING EARLY MEDIEVAL KERALA - Suresh K. M (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Temple is of great importance to medieval historians. In Kerala also temples played a very vital role in the social formation. Even though temples are generally considered as a Brahmanic institution it was not so. Temples was the center of medieval Kerala society which included Brahmanas and non-Brahmanas as well. The present study tries to focus on the non-Brahmana groups who were directly associated with the day-to-day functioning of a temple, i.e. the Sreevallabha temple in Central Travancore. Though there are several important studies on the general aspects of the temples’ role in medieval social formation in Kerala, a specific study on the non-Brahmana employees depended on a Brahmanic temple is still lacking. This attempt is to fill that gap of knowledge by identifying varying non-Brahmana groups, their functions, social status and their relation to temple.